Public administration in the educational space of the Northern Azov region during the period of 1864-1918 years - Shumilova, Iryna; Zolotukhina, Svetlana; Zelenska, Lyudmyla; Sherstneva, Iryna (International Journal of Psychosocial Rehabilitation, 2020)
The Northern Azov region covers primarily those territories of modern Zaporizhia and Donetsk regions of Ukraine where there was a dense residence of Ukrainians, Russians, Bulgarians, Germans, Czechs, Tatars, Greeks, Jewish and other peoples in the second half of the XIX and early XX centuries. This multinational region included the territories of Berdyansk, Melitopol, Mariupol, and the southern part of Alexandrovskiy County. Historically, the Northern Azov region has been formed for many centuries. It is a territory where large-scale historical events related to the residence and movement of many peoples have taken place since ancient times. Here different cultures were born, developed, and perished, whole epochs changed. This feature of the historical destiny of the region was preserved in later periods when the Northern Azov region in connection with the geopolitical and military confrontation became a part of various state formations and was a place of settlement of many peoples and nationalities.